Ions-induced ovalbumin foaming properties enhancement: Structural, rheological, and molecular aggregation mechanism. (March 2022) - Zhang, Ting; Zhang, Min; Gong, Ping; Jiang, Hongyu; Liu, Jingbo; Liu, Xuanting
Abstract: This study aims to evaluate monovalent (Na + ) and divalent (Mg 2+ ) ions regulated ovalbumin (OVA) foaming properties enhancement via the change of protein structural and interfacial properties. The macro and microscopic photographs of samples after homogenization 0 min and 30 min were recorded. Results showed that foaming capacity (FC) significantly increased from 59.44 ± 16.69% to 136.67 ± 11.55% (NaCl) and 117.22 ± 5.36% (MgCl2 ). Accordingly, viscosity and surface intension reduced, whereas the amount of OVA adsorption increased, which suggested that ions could promote adsorption of OVA to air-water interface and further improve the foaming properties. Analogously, surface hydrophobicity (H0 ) increased, which revealed that the improvement of hydrophobic interactions of OVA. Besides, the β-sheet content increased, which indicated larger aggregates formed. Noteworthy, from the results of the interfacial adsorption amount and microscopic photographs, the foaming stability (FS) of samples with divalent ions was better, which could be hypothesized that protein intermolecular interactions via salt bridge may be stronger, while monovalent ions interacted with protein by nonspecific bond. Overall, our study provides a convenient approach of ions regulated structural and foaming properties of OVA, which may be a new strategy in improving the protein interfacial properties in food processing industry. Graphical abstract: Image 1 Highlights: The foaming capacity of ions-induced OVA were twice folded than native OVA. Na + accelerates the adsorption of OVA to the interface through non-specific binding. Mg 2+ strongly bound to OVA through salt bridge and electrostatic shielding effect. MgCl2 induced OVA formed the thicker and denser interfacial film.